Elastic properties of TeO2-B2O3—ZnO-Gd2O3 glasses using non-destructive ultrasonic technique - Chua, Eevon; Mohamed Kamari, Halimah; Zakaria, Azmi; Che Abdullah, Che Azurahanim (National Institute of Materials Physics, National Institute of Optoelectronics, 2016)
The addition of Gd2O3 causes the glass system to be highly ionic resulting in increasing rigidity and the tendency of devitrification. Gd2O3 affects the strength governing the elastic properties of the glass. The elastic moduli of the prepared glasses are expected to increase with the addition of the Gd2O3 due to increasing net molecular weight of prepared glass resulting in strong connectivity and more compactness of the glass network. The objective of this present work is to study the elastic properties of TeO2-B2O3-ZnO doped Gd2O3 using a non-destructive ultrasonic technique. A series of {[(TeO2)0.7(B2O3)0.3]0.7(ZnO)0.3}1-x(Gd2O3)x glasses with x = 0.01, 0.02, 0.03, 0.04 and 0.05 mol were prepared by conventional melt-quenching method. Both longitudinal and shear ultrasonic velocities were measured using a pulse-echo method at a frequency of 5 MHz at room temperature. The elastic moduli (longitudinal modulus, shear modulus, Young’s modulus and Bulk modulus), Poisson’s ratio, Debye temperature, micro-hardness and softening temperature have also been quantified. The experimental results show that the elastic properties depend on the composition of the glass systems and the role of Gd2O3inside the glass network.